THE CONCEPT OF WEALTH IN ISLAM PERSPECTIVE OF THE WORD MAL VERSION OF THE MINISTRY OF RELIGION OF THE REPUBLIC OF INDONESIA IN THE QUR’AN AND ITS TAFSIR - Hamim, Khairul; Mas’ud, Riduan (International Journal of Islamic Khazanah, 2019)
Wealth in Arabic is called mal (mufrad) amwal (jama’). This word with its various derivations is repeated 86 times in 38 surahs in the Qur’an. Wealth is an important part of life that cannot be separated and is always sought to be achieved and owned by humans. For this reason, a clear explanation is needed that can be accepted by all parties. This study uses an interpretation research method by analyzing the word Mal in the version of the Indonesian Ministry of Religion in the Qur’an and its Tafsir. This study formulates that property is everything that is owned in the form of material and can be used to support life (wasilah al-hayah), such as housing, vehicles, equipment, gold, silver, land, animals, even in the form of money, and has value. for the human view.